IMPROVING ENVIRONMENTAL AWARENESS OF MADRASAH STUDENTS THROUGH GUIDANCE AND COUNSELING MANAGEMENT - Sukarman Sukarman; Fikrotul Irtiya; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The widespread environmental damage of today increasingly emphasizes the importance of environmental awareness. The lack of environmental awareness demonstrated by students in their daily school environment indicates a low level of environmental awareness. This study examines the implementation of Guidance and Counseling (GC) services in fostering environmental responsibility among students at Madrasah Aliyah Nahdlatul Muslimin during the 2025/2026 academic year, analyzes the contribution of GC services to the development of students’ environmental care character, and identifies the supporting and inhibiting factors affecting the implementation of GC services in promoting environmental responsibility.This study employed a qualitative approach using a descriptive research design. Data were collected through interviews, observations, and document analysis and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that GC services were implemented through personal, social, academic, career, group counseling, crisis intervention, and mediation services. Improvements in students' environmental character were reflected in maintaining classroom and school cleanliness, caring for plants, supporting school greening programs, utilizing waste segregation facilities, and maintaining hygiene through adequate sanitation facilities. Supporting factors included exemplary behavior of teachers, adequate facilities, stakeholder collaboration, and active student participation. Conversely, the major barriers were the lack of systematic integration between GC programs and environmental education, students' limited environmental awareness and behavioral consistency, insufficient counseling time, and the influence of external environmental factors.